Scenography of the Show Hari Terakhir Mangkutak as a Media for Appreciation - Inggit Prastiawan; Irwansyah Irwansyah; Erizon Erizon (Gondang: Jurnal Seni dan Budaya, 2022)
The artistic creation of the stage as a medium for appreciation of performing arts is a manifestation of the author's interest in performing arts. Aka Bodi Theater is one of the theater groups developing in the city of Medan which often performs sui generis repertoire. Despite the limited facilities for holding performances, Medan City still has several groups that propose unusual performance styles. Performances from the Aka Bodi Theater group generally use an intense stage with the public, but due to the lack of artistry in the performances, through this article the author wants to explain the scenographic concept of the Mangkutak Last Day performance. The author created an artistic design for a proscenium stage prepared with all the artistic elements that support the performance. The choice of an eclectic style which is packaged with a stage set that has performance elements complemented by stage artistic value, is intended to harmonize modern developments and foster innovation values, as well as philosophical values presented in the performance in a unified artistic production. So that this article can be an intellectual contribution in terms of ideas, interpretation of the concept of scenography into the artistic space of performance by creating a concept of appreciation for performing arts.